The Design of Skynesia Adventure Mobile Game Application Using Game Development Life Cycle Method as an Alternative Learning Media for High School Students - Emas Dai Ashshiddiiqi; Nia Ambarsari; Ekky Novriza Alam (School of Industrial and System Engineering, Telkom University, 2023)
Skynesia Adventure is a mobile-based gaming application designed to make the learning process moreenjoyable and interactive, while also generating revenue for the startup Skynesia. The results of thequestionnaire indicate that, on average, potential users prefer educational games that focus on science orSTEM subjects, and some users believe that educational games can enhance their knowledge of science orSTEM while having fun. This research utilized the game development life cycle theory in the developmentof the gaming application, and questionnaires were used as a method for designing and testing the applicationto ensure its usability by users. After the completion of the gaming application design, it went through twophases of testing and evaluation: alpha testing through Unit Testing, and beta testing through the UserExperience Questionnaire - Short Version. The results of these tests indicated that Skynesia Adventureachieved a score of 2.29 for both pragmatic and hedonic qualities. Therefore, the Skynesia Adventure gamingapplication can be considered to provide users with a highly satisfactory user experience. The benefits ofSkynesia Adventure include providing a more enjoyable and interactive learning experience by combininggaming elements with scientific or STEM knowledge.